De la contagion à la cogitation : le zombie évolutif de la télévision - Paul Scott (ReS Futurae)
The figure of the zombie is as versatile as it is enduring, and this article analyses two recent television shows featuring versions of the undead that belong to a worldwide wave of conscious, sentient zombies. The returned of Resurrection (US, 2014-2015) and Glitch (Australia, 2015-2019) are humane, ostracized figures who encounter prejudice and suspicion from localized communities in rural Missouri and in the Victorian outback. In their respective reconfigurations of the classic zombie narrative of menacing invaders, these shows cast the undead as sympathetic protagonists who stand as powerful metaphors for socioeconomic migration and marginalization.